Overview of Dairy Breeding and Animal Health Management - Assefa, Getnet; Mekonnen, Kindu; Gebreyes, Million; Bezabih, Melkamu; Seifu, Haimanot (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Presentation in Addis Ababa, Ethiopia, March 27-28, 2023. Overview of Dairy Breeding and Animal Health Management